Elite athletes` experiences with, and perceptions of nonspecific goals: a qualitative exploration - Williamson, O.; Bird, M. D.; Bennett, K. J. M.; Jackman, P. C.; Swann, C. (International Journal of Sport and Exercise Psychology, 2025)
Specific goals are recommended and used widely in sport. However, athletes have reported using nonspecific goals in the process underlying the occurrence of flow, an optimal psychological state. Nevertheless, athletes` overall use of nonspecific goals in sport has yet to be investigated. Therefore, we conducted a qualitative study to understand athletes` experiences and perspectives on nonspecific goals in sport. Seventeen athletes (M age = 28.06, SD = 9.77) participated in semi-structured interviews. Our content analysis found that athletes used various types of nonspecific goal across several sporting contexts. Performance/situation uncertainty, individual differences in stress appraisal, and to account for factors outside of the athletes control all influenced the setting of nonspecific goals. Athletes reported that all types of nonspecific goals could enhance objective performance, enjoyment, satisfaction, engagement, and optimise feelings of challenge, while reducing perceptions of pressure. Conversely, athletes believed that all nonspecific goals could elicit maladaptive motivational responses and lack structure, which could result in difficulty with tracking progress. Differences between certain types of nonspecific goals were also found. Specifically, open goals were reported in situations of novelty/exploration to gauge performance, whereas do-your-best goals were perceived as a constant, yet minimal expectation. Finally, some athletes suggested that do-your-best goals were overly vague, whereas do-your-best and as-well-as-possible goals could cause overexertion. This study extends knowledge regarding the importance of nonspecific goals in sport, while emphasising the necessity for researchers and applied practitioners to consider contextual factors, individual differences, and targeted outcomes of interest when using nonspecific goals.